PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 5E TERHADAP BERPIKIR KRITIS SISWA KELAS IV PADA PEMBELAJARAN BAHASA INDONESIA - Mochammad Aprieyadi Phermadi; Lutfi; Fitria Rosmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore how the Learning Cycle 5E model can enhance elementary students’ critical thinking skills in Indonesian language learning. The research used a quantitative approach with an experimental design of Posttest Only Control Group. The subjects were 60 fourth-grade students from SDN Pondok Labu 02 Jakarta Selatan, divided into an experimental group and a control group. The instrument used was a critical thinking test consisting of four indicators: interpretation, analysis, evaluation, and inference. The results showed that the experimental group achieved an average posttest score of 85.09%, while the control group scored 67.50%. The t-test result (tcount = 5.450 > ttable = 1.325, sig = 0.000 < 0.05) indicated a significant effect of the Learning Cycle 5E model. The R Square value of 0.507 suggests that the model contributed about 50.7% to the improvement in students’ critical thinking skills. In conclusion, applying the Learning Cycle 5E model effectively supports students in developing critical and active thinking during Indonesian language learning.